No evidence of major effects in several Toll-like receptor gene polymorphisms in rheumatoid arthritis - Jaen, Olivier; Petit-Teixeira, Elisabeth; Kirsten, Holger; Ahnert, Peter; Semerano, Luca; Pierlot, Céline; Cornelis, François; Boissier, Marie-Christophe; Falgarone, Geraldine (Arthritis research & therapy, 2009)
INTRODUCTION\backslashr\backslashnThe objective was to study the potential genetic contribution of Toll-like receptor (TLR) genes in rheumatoid arthritis (RA). TLRs bind to pathogen-associated molecular patterns, and TLR genes influence both proinflammatory cytokine production and autoimmune responses. Host-pathogen interactions are involved in RA physiopathology.\backslashr\backslashnMETHODS\backslashr\backslashnWe tested SNPs of five TLR genes (TLR9, TLR2, TLR6, TLR1, and TLR4) in a cohort of 100 French families with RA. Genotypes were analyzed using the transmission disequilibrium test. As TLR2, TLR6, and TLR1 are located on chromosome 4, we determined the haplotype relative risk. Analyses were performed in subgroups defined by status for rheumatoid factor, anti-cyclic citrullinated peptide autoantibodies, and erosions.\backslashr\backslashnRESULTS\backslashr\backslashnWe found no disequilibrium in allele transmission for any of the SNPs of the five TLR genes. In subgroup analyses, no associations were detected linking TLR9, TLR2, or TLR9/TLR2 to rheumatoid factor, anti-cyclic citrullinated peptide autoantibodies, or erosions. Haplotype analysis of the polymorphisms showed no haplotype associations in any of the subgroups.\backslashr\backslashnCONCLUSIONS\backslashr\backslashnWe found no evidence of major effects of TLR gene polymorphisms in RA, although we tested different TLR phenotypes. Moreover, no associations were noted with autoantibody production or erosions.